2018
DOI: 10.1080/03630242.2017.1414101
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lavender cream with or without footbath on sleep quality and fatigue in pregnancy and postpartum: a randomized controlled trial

Abstract: Lavender cream with or without footbath may improve sleep quality in pregnancy and postpartum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 32 publications
1
35
0
4
Order By: Relevance
“…Two recent studies reported that lavender relieved job-related stress among nurses [6] and ameliorated depression, anxiety and stress among pregnant women [7], whereas another study published in the same year reported no signi cant psychological or physiological effects of lavender aroma inhalation after coronary artery bypass surgery [8]. These studies reported con icting results despite being well-designed, placebo-controlled studies with an adequate sample size (n = 60-141).…”
Section: Introductionmentioning
confidence: 99%
“…Two recent studies reported that lavender relieved job-related stress among nurses [6] and ameliorated depression, anxiety and stress among pregnant women [7], whereas another study published in the same year reported no signi cant psychological or physiological effects of lavender aroma inhalation after coronary artery bypass surgery [8]. These studies reported con icting results despite being well-designed, placebo-controlled studies with an adequate sample size (n = 60-141).…”
Section: Introductionmentioning
confidence: 99%
“…Where the studies even have shown the significant effects on the increased 2 nd stage of the sleep. Where the sleep was successfully induced with the elevation in the mood, and there were no side effects reported, which indirectly gives a betterment of depression by modulating the circadian rhythm [46].…”
Section: Stress Hormones and Cytokinesmentioning
confidence: 93%
“…Furthermore, interspecies differences in anxiolytic effects have been observed with the main anxiolytic effects being due to the activity of linalool and linalyl acetate [126]. The oils of Lavandula varieties have also proven to be effective in reducing stress, anxiety, and depression in patients in an array of clinical settings such as hospice cancer patients, patients awaiting treatment in a dental office, male and female volunteers shown anxiety-provoking film clips, pregnant women through use of L. angustifolia essential oil-containing cream, as well as reduction of anxiety and heart rate in patients undergoing elective cosmetic procedures [127][128][129][130][131]. One study suggested that the reduction of stress symptoms upon inhalation of the essential oils may be partially due to the reduction in salivary cortisol levels, and to protection against oxidative stress by increasing free radical scavenging activity [132,133].…”
Section: Psychological Implicationsmentioning
confidence: 99%